Experimental theatre in Old Town, Alexandria, Virginia - Mikkola-Parnanen, Marja (Virginia Polytechnic Institute and State University, 1995)
Theatre would be radical, arousing, inspiring, challenging popular emotion, presenting native problems. Human strength and aspiration would go there for inspiration." - Frank Lloyd Wright- Bruce Brooks Pfeiffer, Gerald Nordland: Frank Lloyd Wright in the realm of ideas, Bynum, NC: Southern Illinois University Press, 1988, page 100 Master of Architecture